Preparation and characterization of Co(II), Ni(II) and Cu(II) complexes of a ligand containing 1,3,4-thiadiazole groups - Öztürk, Ömer Faruk; Cansız, Ahmet; Koparır, Metin (Springer Netherlands, 2007)
(1R,2R)-1,2-bis-(5-amino-1,3,4-thiadiazole-2-yl)ethane-1,2-diol (L) has been prepared by the reaction of thiosemicarbazide with (2R,3R)-(+)-tartaric acid (I) and phosphorous oxychloride, and its complexes with Co(II), Ni(II) and Cu(II) have been obtained. The structures of the ligand and its complexes have been established by i. r., 1 H- and 13 C-n.m.r. spectra, u.v.-vis-nir spectroscopy, elemental analyses, T.g.-D.t.a. and magnetic susceptibility measurements. © Springer 2007.
Keywords: Chemical analysis; Copper alloys; Magnetic susceptibility; Nitrogen compounds; Reaction kinetics; Ultraviolet spectroscopy; Thiadiazole groups; Thiosemicarbazide; Ligands